A Novel Polysaccharide from Blackened Jujube: Structural Characterization and Immunoactivity - Meng Meng; Fang Ning; Xiaoyang He; Huihui Li; Yinyin Feng; Yanlong Qi; Huiqing Sun (Foods, 2025)
Previously, research adopted an ultrasound-assisted extraction method to isolate crude polysaccharide from blackened jujube, followed by preliminary structural identification of the purified polysaccharide (BJP). This manuscript analyzed the accurate structure and immunomodulatory activity of BJP. Further structural identification indicated that BJP was mainly composed of →3)-α-L-Araf-(1→, →3,5)-α-L-Araf-(1→, →3)-β-D-GalpA-(1→, →2,4)-β-D-Galp-(1→, →4)-β-D-GalpA-(1→, →3)-α-L-Rhap-(1→ and →3,4)-α-L-Rhap-(1→. The immunomodulatory effects of BJP were examined using a mouse model with immunosuppression induced by cyclophosphamide. The findings suggested that BJP could relieve the condition of immunosuppressed mice. BJP could inhibit decreases in the body weight and organ index of mice, and HE staining showed that BJP could alleviate the harm to spleen and thymus tissues. BJP enhanced the secretion of interferon-γ (IFN-γ), tumor necrosis factor-α (TNF-α), interleukin-2 (IL-2), interleukin-6 (IL-6), immunoglobulin A (IgA), and immunoglobulin G (IgG) in serum. It also reduced liver oxidative stress by increasing superoxide dismutase (SOD), catalase (CAT), and glutathione (GSH) activities, while lowering malondialdehyde (MDA) levels. Moreover, BJP contributed to the maintenance of gut homeostasis by stimulating the generation of short-chain fatty acids in the cecal contents. The study aims to establish a solid basis for the comprehensive development of blackened jujube and furnish a theoretical framework for its polysaccharides’ role in immune modulation.